Development and Evaluation of a Model for Modular Automation in Plant Manufacturing - Uwe Katzke; Katja Fischer; Birgit Vogel-Heuser (Journal of Systemics, Cybernetics and Informatics, 2005)

(untitled)
The benefit of modular concepts in plant automation is seen ambivalent. On one hand it offers advantages, on the other hand it also sets requirements on the system structure as well as discipline of designer. The main reasons to use modularity in systems design for automation applications in industry are reusability and reduction of complexity, but up to now modular concepts are rare in plant automation. This paper analyses the reasons and proposes measures and solution concepts. An analysis of the work flow and the working results of some companies in several branches show different proposals of modularity. These different proposals in production and process engineering are integrated in one model and represent different perspectives of an integrated system.